Media freedom and the “transition” era in Mozambique: 1990-2000 - Bussotti, L. (Media freedom and right to information in Africa, 2015)
In this article the author aims at analysing the evolution of Mozambican journalism, since 1990 (when the new Constitution was approved) until today. The key hypothesis is that Mozambican journalism has been strictly related to Mozambican democracy, and that in 1999-2000 there has been important facts which have determined the option for different avenues from the side of private and public press. After giving a short framework on the political situation in Mozambique, the article focuses its attention on the legal basis of Mozambican media freedom, stressing the limitations that, till today, it continues to register.